2002
DOI: 10.1038/sj.jhh.1001385
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension control and medication increase in primary care

Abstract: Over half of treated patients with hypertension are not well controlled. However, little is known about physicians' prescribing behaviour for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Other studies have indicated the doctor-patient relationship as an important factor affecting the control of hypertension. 20,21 In the present study, the likelihood of poor BP control was increased when the GP was aged 50 years and older. Moreover, in a previous study, we found that adherence to antihypertensive treatment was lower in newly treated patients who were followed by older physicians.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Other studies have indicated the doctor-patient relationship as an important factor affecting the control of hypertension. 20,21 In the present study, the likelihood of poor BP control was increased when the GP was aged 50 years and older. Moreover, in a previous study, we found that adherence to antihypertensive treatment was lower in newly treated patients who were followed by older physicians.…”
Section: Discussionmentioning
confidence: 45%
“…Other studies have evaluated barriers and facilitators to the management of hypertension in primary care, including physician-related factors, ethnicity of the patients, co-morbidity, and continuity of care. [20][21][22][23][24] In this study, several factors appear to affect the risk of uncontrolled BP in the primary care setting: the patient's age, the presence of comorbidities such as diabetes mellitus and/or target organ damage (ie previous MI), the number of other medications currently being taken by the patient, and the GP's age. How these factors affect BP control is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in view of the relatively low levels of treatment intensity at baseline, most observed failures to change therapy are probably due to poor quality of care or clinical inertia (12). Proposed explanations for clinical inertia include physicians' overestimation of their adherence to guidelines (12) or acceptance of elevated risk factor levels in their patients (30), lack of training on achieving therapeutic goals, possible lack of motivation in clinicians to treat asymptomatic chronic conditions (12), pharmacotherapy pill burden (31), acute symptoms that supersede risk factor management, and time limitations (32). Quality improvement strategies that incorporate more clinically specific measures of "appropriate care," such as those examined in our study, into performance feedback or physician reminder systems (12) may be more effective in overcoming these barriers and improving risk factor levels.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The lack of appropriate medication therapy intensification by clinicians is a primary reason that patients fail to reach recommended targets for conditions such as hypertension, hyperglycemia, and hyperlipidemia. [26][27][28][29][30][31][32] Low rates of clinician responsiveness or "clinical inertia" in the face of elevated CVD risk factor levels have been associated with poorer levels of risk factor control. 30,31,33,34 Another significant contributor to the underutilization of medications is the lack of patient adherence to the drug regimens prescribed by clinicians.…”
Section: Introductionmentioning
confidence: 99%